Family Size and Boy-Child Drop Out Rate in Public Day Secondary Schools in Makueni County, Kenya - Mueni, Rose K.; Maithya, Redempta (Machakos University, 2018)
School dropout for both boys and girls is an area of concern not only in Kenya but also in the whole world. The government of Kenya has placed certain measures to give basic education to its citizens by introducing Free Primary Education and Free Day Secondary Education. Despite this effort, students both boys and girls have been dropping out of school. The main purpose for the study was to investigate the influence of family size on boy-child dropout in public day secondary schools in Makueni County, Kenya. The study adopted descriptive survey research design. The target population comprised of all 11 day secondary schools in Kilungu Sub-County, Makueni County. Simple random sampling technique was used to select a sample size of 6 public day secondary schools out of 11; 6 principals and 6 class teachers while 300 boys were selected making a total of 318 respondents. Data was collected using questionnaires, interviews and document analysis. The collected data was analyzed using both descriptive and inferential statistics using the Statistical Package for Social Sciences (SPSS). The findings of the study were that family size influences boy-child drop out from public day secondary schools (r =+0.512). From the findings of this study the researchers recommended that the parents should be sensitized on the importance of boy-child education and that the government should provide funds to support boys-child education from poor families. Key words: Family size, boy-child dropout, day secondary schools.
Keywords: Boy-child dropout